Proposed new interior design of Felda D’Saji Restaurant for Felda D’Saji Sdn Bhd at No. 40, Lorong Cheah Cheang Lim, Off Jalan Raja Dihilir, 31350 Ipoh, Perak / Siti Asiah Tokichor - Tokichor, Siti Asiah (Faculty of Architecture, Planning and Surveying, 2010)
Nowadays, people becomes more alert on design and style. There are many themed restaurants, fine dining restaurant in Malaysia that can fulfill people wants in design scope. Besides elements of asthethic, the propotion of the space arrangement also becomes important in designing restaurant. A good space planning helps to give quality services to customers although the food quality serving is the main factor customers will care about. All this elemnts will give good interpretation of the restaurant itself to people and also market their product widely. Actually, at the same time people will know the standard level of the restaurant. This proposal is about designing restaurant that provides quality on serving customers, space arrangement and environment of the restaurant which is customer can feel comfort when having the meals. The client of this project is FeldaD’Saji. So, the outcomes of the design will deliver client’s wants and fulfill the requirement needs into design and market their products.